Eosinophils in inflammatory bowel disease pathogenesis: an ROS-centric view - Tomii, Toshihiro; Kano, Gen (Frontiers in Allergy, 2025)
Eosinophils (Eos), long recognized for their roles in allergy and helminth defense, are now emerging as key players in gastrointestinal immune regulation. In inflammatory bowel disease (IBD), eosinophils are frequently elevated in both blood and intestinal tissues, yet their functional significance has been underexplored. This review reexamines the role of eosinophils in IBD pathogenesis, integrating recent insights into mucosal immunity and tissue homeostasis. We outline the shift in perspective from viewing eosinophils solely as inflammatory effectors to recognizing their dual roles in inflammation and repair. Clinical and experimental findings reveal correlations between eosinophil abundance, activation markers, granule protein release, and disease activity in IBD. Central to our model is the regulatory function of eosinophil-derived reactive oxygen species (ROS), particularly hydrogen peroxide, in maintaining intestinal barrier integrity. Dysregulation of ROS—due to dysbiosis or genetic variants—may impair healing and exacerbate inflammation. We further highlight Siglec-8, an inhibitory receptor on eosinophils that induces apoptosis in response to Neu5Ac-containing sialic acids. This pathway may be disrupted by Neu5Gc, a non-human sialic acid abundant in red meat, potentially linking Western diets to impaired eosinophil regulation. These findings suggest new therapeutic directions targeting Siglec-8 and ROS balance to modulate eosinophil activity and restore intestinal immune homeostasis in IBD. These insights may also help bridge traditionally distinct disease paradigms by highlighting a potential common pathogenic mechanism of epithelial barrier dysfunction and dysregulated eosinophil activation shared between allergic diseases (e.g., asthma, eosinophilic esophagitis) and IBD.